A Mxene-loaded hydrophobic persimmon fiber aerogel and its preparation method and application

By introducing Mxene into persimmon fibers and hydrophobic modification, a hydrophobic persimmon fiber aerogel loaded by Mxene is formed, which solves the problem of poor formaldehyde removal effect of traditional adsorbent materials under high humidity, and achieves efficient formaldehyde adsorption and efficient utilization of agricultural resources.

CN119175085BActive Publication Date: 2025-03-14SHANGHAI HOPE TREE BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411698174.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Existing adsorbent materials such as activated carbon have poor formaldehyde removal effect in high humidity environments, and persimmons are wasted as resources, and the added value of traditional persimmon processing products is low.

Method used

By forming hydrogen bond cross-linking with the hydroxyl groups in the persimmon fibers, and hydrophobic modification is obtained through electrostatic attraction to form a hydrophobic persimmon fiber aerogel loaded with Mxene. The material exhibits a sheet structure and hydrophobicity, which enhances the formaldehyde adsorption effect.

Benefits of technology

The formaldehyde removal effect is significantly improved in high humidity environments, and the efficient utilization of materials is achieved, with high practical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175085B_ABST
    Figure CN119175085B_ABST
Patent Text Reader

Abstract

The present invention discloses a Mxene-loaded hydrophobic persimmon fiber aerogel, a preparation method and an application thereof. The Mxene-loaded hydrophobic persimmon fiber aerogel of the present invention presents a lamellar structure, which is convenient for the adsorption of formaldehyde, and at the same time, through the modification of hydrophobicity, the formaldehyde removal effect in a high humidity environment is improved. The present invention forms a lamellar structure aerogel by self-assembly without adding an additional cross-linking agent by forming hydrogen bonds with the hydroxyl groups of the persimmon fiber through the abundant groups on the surface of Mxene. The abundant pores are conducive to the adsorption of formaldehyde, and at the same time, the hydrophobic modification improves the formaldehyde removal effect of the material in a high humidity environment, and has more practical application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of formaldehyde removal and relates to a Mxene-loaded hydrophobic persimmon fiber aerogel and a preparation method and application thereof. Background Art

[0002] Formaldehyde is a colorless gas with a strong pungent odor. It is easily soluble in water, alcohol, and ether. Due to its active chemical properties, formaldehyde is widely used in daily life, such as urea-formaldehyde resin glue used in furniture, formaldehyde-containing additives in coatings, and fixatives and finishing agents in fiber fabrics.

[0003] However, formaldehyde is a highly toxic substance, ranking second on my country's priority list of toxic chemicals. It has also been identified by the World Health Organization as a carcinogen and teratogen, a recognized source of allergic reactions, and one of the potential strong mutagens.

[0004] Adsorption can quickly remove formaldehyde from the air. However, traditional adsorption materials such as activated carbon have problems such as poor porosity and low adsorption capacity. Persimmon is a native fruit in my country. The domestic persimmon planting area ranks first in the world, accounting for about 93.92% of the total persimmon planting area in the world (15.7474 million mu). Due to the storage resistance of persimmon, the fresh eating period is very short, and the types of other deep-processed products of persimmon are limited, such as some processed into persimmon cakes, persimmon wine, beverages, etc. with low added value, and a large number of persimmons are wasted. Persimmon contains a large amount of tannins and fibers, which have a certain adsorption effect on formaldehyde, but the effect is general. Mxene is an emerging two-dimensional material with a high specific surface area and excellent mechanical properties. It can improve the adsorption performance of the material, but it has strong hydrophilicity. During the adsorption process, water molecules can reduce the adsorption effect of the material on formaldehyde, resulting in poor formaldehyde removal effect in high humidity environment in summer. Therefore, it is urgent to develop an efficient formaldehyde adsorption material based on persimmon and Mxene to achieve efficient utilization of agricultural resources. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the present invention provides a hydrophobic persimmon fiber aerogel loaded with Mxene, based on the formation of hydrogen bond cross-links between hydroxyl groups in persimmon fiber and Mxene, and obtains hydrophobic modification through electrostatic attraction, wherein the persimmon fiber and Mxene self-assemble to form an aerogel with a lamellar structure, and the material presents a three-dimensional orderly arrangement, which is convenient for the adsorption of formaldehyde. At the same time, the positively charged hydrophobic long-chain macromolecules are combined with the negatively charged persimmon fiber to give the surface hydrophobic properties, thereby improving the formaldehyde removal effect in a high humidity environment.

[0006] The invention provides a Mxene-loaded hydrophobic persimmon fiber aerogel. The Mxene-loaded hydrophobic persimmon fiber aerogel is obtained by cross-linking persimmon fibers with Mxene and presents an orderly arranged lamellar structure.

[0007] The present invention also provides a method for preparing a hydrophobic persimmon fiber aerogel loaded with Mxene, the method comprising the following steps:

[0008] (1) Immerse the persimmon powder in a 1% by mass sodium hydroxide solution and reflux heat and stir.

[0009] (2) Add H2O2 solution, reflux and stir, then filter under reduced pressure to obtain the filter residue, and dry it in an oven at 50°C.

[0010] (3) The filter residue and Ti3AlC2 powder were dispersed in 9M hydrochloric acid solution, ultrasonically mixed, LiF was added, stirred at 40°C, filtered and washed to obtain mxene cross-linked persimmon fiber aerogel.

[0011] (4) dispersing the mxene cross-linked persimmon fiber aerogel in pure water, ultrasonicating and adding a modifier for modification.

[0012] (5) freeze-drying the modified aerogel to obtain a hydrophobic persimmon fiber aerogel loaded with Mxene.

[0013] In step (1), the mass / volume ratio of the persimmon powder to the NaOH solution is (1-5) g: (1-20) mL; preferably, 1 g: 15 mL.

[0014] In step (1), the reflux heating temperature is 100°C-150°C; preferably, 100°C.

[0015] In step (1), the reflux heating time is 1 h-4 h; preferably, 2 h.

[0016] In step (2), the reflux heating temperature is 60°C-90°C; preferably, 70°C.

[0017] In step (2), the reflux heating time is 1 h-4 h; preferably, 1 h.

[0018] In step (2), the volume fraction of H2O2 added is 5%-20%; preferably, it is 10%.

[0019] In step (3), the weight ratio of the filter residue to the Ti3AlC2 powder is 10:1-50:1; preferably, it is 10:1.

[0020] In step (3), the mass ratio of Ti3AlC2 to LiF is 1:1-1:10; preferably, 1:2.

[0021] In step (3), the volume ratio of the mass of Ti3AlC2 to hydrochloric acid is 1g:10mL-1g:50mL; preferably, it is 1g:20mL.

[0022] In step (3), the stirring time is 20 h to 30 h; preferably, 24 h.

[0023] In step (4), the mass ratio of the gel to pure water is (1-20):(1-100); preferably, it is 1:30.

[0024] In step (4), the modifier is one of hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride, or a mixture thereof.

[0025] In step (4), the mass ratio of the gel to the modifier is (1-2):(1-10); preferably, it is 1:5.

[0026] In step (4), the ultrasonic time is 1 h-4 h; preferably, 2 h.

[0027] In one embodiment, the method of the present invention comprises the following steps:

[0028] (1) Cut persimmons into pieces and dry them at 50℃.

[0029] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of the powder in 150 mL of 1% NaOH solution and heat under reflux at 100 °C with stirring for 2 h.

[0030] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0031] (4) Weigh the dried filter residue and Ti3AlC2 powder and disperse them in 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain mxene cross-linked persimmon fiber aerogel.

[0032] (5) Weigh the MXene cross-linked persimmon fiber aerogel, disperse it in pure water, and then slowly add the modifier. Ultrasonicate for 2 hours.

[0033] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0034] The present invention also provides a Mxene-loaded hydrophobic persimmon fiber aerogel prepared by the method.

[0035] The present invention also provides application of the Mxene-loaded hydrophobic persimmon fiber aerogel in formaldehyde removal.

[0036] The beneficial effects of the present invention are: hydrogen bonds are formed between the abundant groups on the surface of Mxene and the hydroxyl groups of persimmon fiber, and a lamellar structure aerogel is self-assembled without adding an additional cross-linking agent. The abundant pores are conducive to formaldehyde adsorption. At the same time, the hydrophobic modification improves the formaldehyde removal effect of the material in a high humidity environment, and has more practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The SEM images of the aerogels prepared in Examples 1-6;

[0038] Figure 2 N2 adsorption and desorption diagrams of aerogels prepared in Examples 1-6;

[0039] Figure 3 The formaldehyde removal effect of aerogels of Control Example 1 and Examples 1-6 in a low humidity environment;

[0040] Figure 4 The formaldehyde removal effect of aerogels of Control Example 1 and Examples 1-6 in a high humidity environment. DETAILED DESCRIPTION

[0041] The present invention is further described in detail with reference to the following specific examples and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art and are not particularly limited by the present invention.

[0042] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0044] Example 1

[0045] (1) Cut persimmons into pieces and dry them at 50℃.

[0046] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0047] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0048] (4) Weigh 10 g of the dried filter residue and 1 g of Ti3AlC2 powder and disperse them in 20 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 2 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain mxene cross-linked persimmon fiber aerogel.

[0049] (5) Weigh 2 g of MXene cross-linked persimmon fiber aerogel and disperse it in 60 mL of pure water, then slowly add 10 g of hexadecyltrimethylammonium bromide and ultrasonicate for 2 hours.

[0050] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0051] Example 2

[0052] (1) Cut persimmons into pieces and dry them at 50℃.

[0053] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0054] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0055] (4) Weigh 5 g of the dried filter residue and 0.5 g of Ti3AlC2 powder and disperse them in 10 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 1 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain Mxene cross-linked persimmon fiber aerogel.

[0056] (5) Weigh 2 g of MXene cross-linked persimmon fiber aerogel and disperse it in 60 mL of pure water, then slowly add 10 g of hexadecyltrimethylammonium chloride. Ultrasonicate for 2 hours.

[0057] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0058] Example 3

[0059] (1) Cut persimmons into pieces and dry them at 50℃.

[0060] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0061] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0062] (4) Weigh 20 g of the dried filter residue and 2 g of Ti3AlC2 powder and disperse them in 40 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 4 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain Mxene cross-linked persimmon fiber aerogel.

[0063] (5) Weigh 3 g of MXene cross-linked persimmon fiber aerogel and disperse it in 90 mL of pure water, then slowly add 15 g of hexadecyltrimethylammonium bromide. Ultrasonicate for 2 hours.

[0064] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0065] Example 4

[0066] (1) Cut persimmons into pieces and dry them at 50℃.

[0067] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0068] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0069] (4) Weigh 10 g of the dried filter residue and 1 g of Ti3AlC2 powder and disperse them in 20 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 2 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain Mxene cross-linked persimmon fiber aerogel.

[0070] (5) Weigh 3 g of MXene cross-linked persimmon fiber aerogel and disperse it in 90 mL of pure water. Then slowly add 10 g of hexadecyltrimethylammonium bromide and 5 g of hexadecyltrimethylammonium chloride. Ultrasonicate for 2 hours.

[0071] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0072] Example 5

[0073] (1) Cut persimmons into pieces and dry them at 50℃.

[0074] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0075] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0076] (4) Weigh 10 g of the dried filter residue and 1 g of Ti3AlC2 powder and disperse them in 20 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 2 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain Mxene cross-linked persimmon fiber aerogel.

[0077] (5) Weigh 3 g of MXene cross-linked persimmon fiber aerogel and disperse it in 90 mL of pure water. Then slowly add 5 g of hexadecyltrimethylammonium bromide and 10 g of hexadecyltrimethylammonium chloride. Ultrasonicate for 2 hours.

[0078] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0079] Example 6

[0080] (1) Cut persimmons into pieces and dry them at 50℃.

[0081] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0082] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0083] (4) Weigh 10 g of the dried filter residue and 1 g of Ti3AlC2 powder and disperse them in 20 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 2 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain Mxene cross-linked persimmon fiber aerogel.

[0084] (5) Weigh 2 g of MXene cross-linked persimmon fiber aerogel and disperse it in 60 mL of pure water. Then slowly add 5 g of hexadecyltrimethylammonium bromide and 5 g of hexadecyltrimethylammonium chloride. Ultrasonicate for 2 hours.

[0085] (6) Filter, wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded hydrophobic persimmon fiber aerogel.

[0086] Comparative Example 1

[0087] (1) Cut persimmons into pieces and dry them at 50℃.

[0088] (2) Crush the dried persimmon pieces to obtain persimmon powder. Immerse 10 g of persimmon powder in 150 mL of 1% NaOH solution and reflux at 100 °C with stirring for 2 h.

[0089] (3) After cooling to 70°C, add 15 mL of 10% H2O2 solution and stir under reflux at 70°C for 1 h. Filter under reduced pressure and wash with pure water until neutral to obtain a filter residue. Dry the obtained filter residue in a drying oven at 50°C for 24 h.

[0090] (4) Weigh 10 g of the dried filter residue and 1 g of Ti3AlC2 powder and disperse them in 20 ml of 9M hydrochloric acid. Ultrasonicate them under argon atmosphere until a uniform suspension is formed. Add 2 g of LiF, stir at 40 °C under argon atmosphere for 24 h, filter and wash to obtain Mxene cross-linked persimmon fiber aerogel.

[0091] (5) Filter and wash with pure water and ethanol three times respectively, and freeze-dry to obtain the Mxene-loaded persimmon fiber aerogel.

[0092] Experimental results of Examples 1-6:

[0093] SEM: Through SEM, it can be observed that the aerogels prepared in Examples 1-6 of the present invention all have a multilayer structure, and the surface is covered with uneven flaky structures.

[0094] Example 7 Nitrogen adsorption and desorption test

[0095] The adsorption-desorption isotherm of N2 at 298 K was tested using the adsorption instrument ASAP 2460. The specific experimental results are shown in Figure 2The persimmon fiber aerogels prepared in Examples 1-6 of the present invention all have a mesoporous structure, and the aerogel prepared in Example 4 of the present invention has the best adsorption performance.

[0096] Example 8 Formaldehyde adsorption experiment 1

[0097] The temperature and humidity in the 200L sealed cabin were controlled at 27℃ and 30%. The heating table was preheated to 80℃ in the cabin. 150ul of formaldehyde solution was dropped into a glass petri dish and placed on the heating table for 30 minutes to completely volatilize the formaldehyde. Then 10g of aerogel sample was placed in it. The atmospheric sampler was used to sample at different time points and the values ​​were recorded. Figure 3 As shown, compared with the blank group without aerogel, the aerogels prepared in Examples 1-6 of the present invention and the aerogel prepared in Control Example 1 (Control Group 1) can effectively remove formaldehyde under dry conditions, and Example 4 of the present invention can remove up to 99% of formaldehyde within 24 hours.

[0098] Example 9 Formaldehyde adsorption experiment 2

[0099] The temperature and humidity in the 200L sealed cabin were controlled at 27℃ and 70%. The heating table was preheated to 80℃ in the cabin. 150ul of formaldehyde solution was dropped into a glass culture dish and placed on the heating table for 30 minutes to completely volatilize the formaldehyde. Then 10g of aerogel sample was placed in it. The atmospheric sampler was used to sample at different time points and the values ​​were recorded. Figure 4 As shown, compared with the blank group without aerogel, the aerogels prepared in Examples 1-6 of the present invention can effectively remove formaldehyde, among which Example 4 of the present invention can still remove 99% of formaldehyde within 24 hours. The formaldehyde removal effect of the aerogel prepared in Control Example 1 (Control Group 1) decays to 50% under high humidity.

[0100] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0101] As used in the present invention, the term "comprising" is an open expression, that is, including the contents specified in the present invention but not excluding other contents.

[0102] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0103] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a hydrophobic persimmon fiber aerogel loaded with Mxene, characterized in that: The method comprises the following steps: (1) immersing persimmon powder in a sodium hydroxide solution with a mass fraction of 1%, and reflux heating and stirring; the mass / volume ratio of the persimmon powder to the sodium hydroxide solution is (1-5) g: (1-20) mL; the reflux heating temperature is 100° C.-150° C.; (2) adding H2O2 solution, reflux heating and stirring, then filtering under reduced pressure to obtain filter residue, and drying in a 50°C oven; the reflux heating temperature is 60°C-90°C; the volume fraction of the added H2O2 solution is 5%-20%; (3) Dispersing the filter residue and Ti3AlC2 powder in a 9M hydrochloric acid solution, ultrasonically mixing them evenly, adding LiF, stirring, filtering and washing at 40°C to obtain Mxene cross-linked persimmon fiber aerogel; the weight ratio of the filter residue and Ti3AlC2 powder is 10:1-50:1; the mass ratio of Ti3AlC2 and LiF is 1:1-1:10; the mass ratio of Ti3AlC2 to the hydrochloric acid solution is 1g:10mL-1g:50mL; (4) dispersing the Mxene cross-linked persimmon fiber aerogel in pure water, ultrasonicating and adding a modifier for modification; the mass ratio of the gel to pure water is (1-20): (1-100); the modifier is one of hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride and a mixture thereof; the mass ratio of the gel to the modifier is (1-2): (1-10); (5) freeze-drying the modified aerogel to obtain a hydrophobic persimmon fiber aerogel loaded with Mxene.

2. The method according to claim 1, characterized in that In step (1), the reflux heating time is 1 h to 4 h.

3. The method according to claim 1, characterized in that In step (2), the reflux heating time is 1 h to 4 h.

4. The method according to claim 1, characterized in that In step (3), the stirring time is 20h-30h.

5. The method according to claim 1, characterized in that In step (4), the ultrasonication time is 1 h to 4 h.

6. The Mxene-loaded hydrophobic persimmon fiber aerogel prepared by the method according to any one of claims 1 to 5, The Mxene-loaded hydrophobic persimmon fiber aerogel is obtained by cross-linking persimmon fibers with Mxene, and presents an orderly arranged lamellar structure.

7. Use of the Mxene-loaded hydrophobic persimmon fiber aerogel as claimed in claim 6 in removing formaldehyde.

Citation Information

Patent Citations

  • Preparation method of polyvinyl alcohol / bagasse nano-cellulose aerogel

    CN108752623A

  • Preparation method of jute fiber-based high-adsorbability hydrophobic cellulose aerogel

    CN114984923A